الاثنوغرافيا السكانية لبلاد "داغستان" شمال شرق القوقاز وأثرها التاريخي في حضارة وتاريخ داغستان - الكرعاوي، نضال أبو جواد أمانة (جامعة القادسية - كلية التربية, 2023)
اتسم تاريخ داغستان القديم والحديث بالغموض ويعود السبب في ذلك كون أن هذا الإقليم تعرض للتغيير المستمر وعبر مراحل تاريخية مختلفة في ملامحه الجغرافية من حيث الحدود والمساحة والتغيير في التكوين العرقي لسكان القوقاز بشكل عام وداغستان بشكل خاص والتغيير السياسي في عدد الخانيات الداغستانية التي حكمت المنطقة وكان أهمها وأكبرها إمبراطورية الخزر، اختص هذا البحث التركيز على شعوب أو سكان القوقاز وأصولهم العرقية، إذ تم الإشارة إلى اهم أصولهم القوقازية من سكان البلاد الأصليين من قبائل اللكز والججن الذين بدورهم انقسموا إلى عدة قبائل أسست لها حكومات محلية، ثم توسع البحث في بيان السكان المستوطنين والذين وصلوا إلى القوقاز عبر الهجرات البشرية الأولى إذ تنوعت وتعددت أصولهم بين الإيرانية والتركية وحتى الأقليات العربية واليهودية في داغستان. The ancient and modern history of Dagestan was characterized by ambiguity, and the reason for this is due to the fact that this region was subject to continuous change and through different historical stages in its geographical features in terms of borders, area, change in the ethnic composition of the population of the Caucasus in general and Dagestan in particular, and the political change in the number of Dagestani khanates that ruled the region and was the most important of them The largest of which is the Khazar Empire. This research specializes in focusing on the peoples or residents of the Caucasus and their ethnic origins. The most important of their Caucasian origins were referred to from the original inhabitants of the country from the Lakz and Jinn tribes, who in turn were divided into several tribes with which local governments were established. They arrived in the Caucasus through the first human migrations, as their origins varied between Iranian, Turkish, and even Arab and Jewish minorities in Dagestan.
Keywords: تاريخ داغستان -- امبراطورية الخزر -- الأعراق البشرية -- سكان القوقاز